PENGARUH DIMENSI MUTU DENGAN RESPON TIME PELAYANAN DI IGD RS SITI HAJAR MEDAN TAHUN 2023 - Batubara, Saiful; sitepu, andriyeni arniel; Br.Sembiring, Sella Elita; Nasution, Windya Sari; Lianto, Depi; Kasim, Felix; tarigan, herri novita (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2024)
The great of carrier is very essential to note because it relates to the carrier with a view to be provided to sufferers. One popular for hospital emergency offerings is carrier excellent manipulate, including response time.The motive of this take a look at to determine the effect of the size of service quality on the reaction time of officials at the emergency room of Siti Hajar hospital, Medan. This studies is a quantitative take a look at with a pass sectional take a look at layout. information collection by means of interview the usage of Questionaire. The populace on this take a look at have been all patients who met the inclusion and exclusion standards with a complete pattern of 90 human beings. data have been analyzed using SPSS with the chi square check to see the impact of independent vareble to based variable.The end result of the research , show that provider get admission to variables have a enormous impact on response time (p = 0.02), provider between individuals have a huge impact on reaction time (p = zero.00), comfort have a substantial effect on response time (p = 0.00), technical competence have a massive effect on reaction time (p = 0.02), records have a good sized impact on reaction time (p = 0.00), performance have a widespread effect on reaction time (p = zero.00), continuity have a sizeable impact on reaction time ( p = zero.02).